Angular momentum transport and temperature Gradient in the middle atmosphere over the tropical Indian region - SARKAR , TK; MUKHOPADHYAYA, RK (MAUSAM, 1989)
The paper deals with the momentum transport and temperature gradient of the middle atmosphere over Balasore and SHAR and their seasonal variation .Weekly RH.200 rocket data for the period 1979-1984 over Balasore and 1979-1982.over SHAR were used to estimate the angular momentum transport and temperature gradient. The results Indicated that the convergence of the westerly momentum by the mean motion towards the equator during post monsoon to pre-monsoon through winter restricted the penetration of the summer hemispheric easterlies Into the winter hemisphere In the lower mesospheric region. During the monsoon, southward eddy transport maintained the mesospheric easterly jet core located poleward of the equator. The temperature gradient and the wind shear analysis showed the barotropic nature of the lower tratosphere throughout the year over tropical Indian region.